Strategi Pembentukan Bilangan untuk Menyederhanakan Perhitungan pada Teorema Pythagoras - Mahfudz Reza Fahlevi (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2021)
This research aims to describe the number formation strategy as an application form of the Pythagorean theorem. A number formation strategy to simplify calculations on the application of the Pythagorean theorem is needed since many mathematical problems solving involve Pythagorean theorem. In some mathematical problems, the Pythagorean theorem is only used as a tool to answer the real problem, for example is a problem in Geometric. This research applies a literature review method. There are three steps should be met to use the number formation strategy in this paper, namely: (1) ensuring that the two side lengths of a right triangle have the same factor, (2) changing integers other than the same factor (if it is the same, select one) becomes the root number, and (3) determining the side in question, if what is being asked is the longest side (hypothenuse) then the two numbers in the same root (radicand) must be added, otherwise if what is being asked is not the hypotenuse (not the longest side), then the two radicans must be subtracted while still being positive.